Pedagogik Hambatan Fisik dan Motorik: Memahami dan Menganalisis Sebab Individu dengan Hambatan Fisik Dan Motorik - Hasanah, Rahmi Diatul; Ronvy, Al Shaffat (Journal of Current Research in Humanities, Social Sciences, and Business, 2025)
This article discusses pedagogy relevant to individuals with physical and motor impairments. The main focus is on understanding and analyzing the underlying causes of these impairments, a crucial step in designing effective educational interventions. Physical and motor impairments can affect students' academic, social, and personal participation and achievement. By identifying the root causes—whether genetic, neurological, environmental, or a combination thereof—educators can develop more appropriate, adaptive, and inclusive pedagogical strategies. This article highlights the importance of a multidisciplinary approach in assessment and intervention, as well as the vital roles of differentiated pedagogy and universal design for learning (UDL).